Não somos diferentes das outras pessoas': a vida cotidiana de mulheres com deficiência mental contada por elas mesmas - Glat, Rosana (1988)
The purpose of this research was investigate the daily life of women who had been labeled mentally handicanped, through their personal biographical reports. In the interviews, the subjects described their routine at home and at the institution, talked about their families, relationships, difficulties in social integration, and also about their physical and learning problems. It became clear in the discourse of this group that a dichotomy existed between the 'inside' world, which included the protective spaces of home and the instituition and the threatening and violent 'outside' world, represented by street. Their social relations were restricted to the people of the 'inside' world: the family, the professionals and the , friends of the instituion, and many subjects mentioned that they feel discriminated against by the people from 'the outside'. Although many women expressed the desire to be in dependent (work 'outside', go out alone, etc), in practice they tend to maintain an extreme degree of dependence on the family. Even though two thirds of the subjects were over 20 years old, they did not seem to have any concrete perspective of living on their own, getting married, or raising their own family. One of the supositions of this study was that the stigma of mental deficiency would be the central theme of the life histories. However, more than. half of the women did not touch on this subject during the interviews, and very few called themselves handicapped. It was sU9gested that the effects of the stigma may have been underestimated in this group due to family and institution overprotection on one hand, and avoidance of the 'outside' world (where this condition would be more openly revealed) on the other. This way, in their daily practice the majority of these women have few opportunities to experience the situation of marginalization. Mental deficiency was analysed as a socially constructed phenomenon, and it is believed that these people function at a much lower level of independence than their organic condition demand , because they have been reinforced for playing the social role of the handicapped. In spite of their common characteristics, each life history proved to be original and unique, showing the fallacy of considering people with mental handicap as a homogeneous and well defined group. Furthermore, except for family dependence, lack of integrated and independent: participation in the community, and restricted love and sexual relationships, these women's lives are not qualitatively different from those of the rest of the population.